160k views
3 votes
Help me to do this problem System by sustitution.
4) y = -3x - 7
-6x - 2y = 14​

User Bitinn
by
4.9k points

1 Answer

5 votes

Answer:

The system of equations has infinite solutions

Explanation:

y = -3x - 7 ⇒ (1)

-6x - 2y = 14 ⇒ (2)

→ Substitute y in equation (2) by equation (1)

∴ -6x - 2(-3x - 7) = 14

→ Simplify the left side

∵ -6x - 2(-3x) - 2(-7) = 14

-6x + 6x + 14 = 14

→ Add the like terms in the left side

∵ (-6x + 6x) + 14 = 14

∴ 0 + 14 = 14

14 = 14

∵ The variable is disappeared and the two sides of the equation equal

∴ The equation has many solutions

→ That means x and y can be any numbers

The system of equations has infinite solutions

User Cristy
by
5.8k points